Muhammad Iqbal's theory of self hood - Abdul Rahim, Adibah (IIUM Press, 2016)
This paper discusses the nature of the self as expounded by Iqbal and how the self grows into a strong and powerful personality. Iqbal does not only preach self-realization by individuals, but his idea also prescribes suppression of individualism for the preclusion of any collective and concerted effort of communal benefit. Iqbal has recognized a necessary relationship between the individual and society. He sees society as a must for the proper growth and development of the human and that it is only in society that man can achieve self-realization. It is at this juncture that this paper also discusses the nature of mutual relationships between the individual and the society wherein man lives, moves, and exists.